Pre-trip expectations and post-trip satisfaction with marine tour interpretation in Hawaii: Applying the norm activation model. Issue 3 (2nd July 2016) - Littlejohn, Kerrie; Needham, Mark D.; Szuster, Brian W.; Jordan, Evan J.
ABSTRACT: This article examines environmental education by focusing on recreationist expectations for interpretation on marine tours, satisfaction with this interpretation and whether expectations were met, and how these perceptions correlate with components of the norm activation model. Recreationists surveyed before and after tours to Molokini, Hawaii ( n = 439) had high pre-trip expectations for interpretation (e.g., about reefs, history), but satisfaction was lower and expectations for many recreationists were not met. Those who had their expectations met had higher problem awareness and ascribed more responsibility (i.e., norm activation) than those who did not, suggesting that interpretation is desired and may promote pro-environmental behavior.